The effect of zinc and probiotics supplements in children under 5 years old with diarrhea - Zhaqila, Qhifani; Ruspandi, Sugeng; Wiedyaningsih, Chairun (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
The 2020 Indonesian Health Profile states that diarrhea is an endemic disease that has the potential to cause extraordinary events. Diarrhea is still one of the contributors to death in Indonesia, especially in children under 5 years old. This study aimed to evaluate the use of zinc and probiotic supplementation on the length of stay (LoS) of patients under 5 years old with diarrhea. It was an observational study using medical records of patients under 5 years old with diarrhea at the Academic Hospital, UGM Yogyakarta in the period of 2021 to 2022. Patient characteristics, including use and medications such as zinc supplementation and probiotics, as well as clinical outcomes including LoS were obtained from 100 medical records. Data were analyzed using chi square from Microsoft Excel 365 & Statistical Program for Social Science (SPSS) with a 95% confidence level (p<0.05). The majority of patients were male (61%) with age range 12-23 mo (47%), 3-4 times frequency of diarrhea (69%), dehydration mild-moderate (89%), and acute diarrhea (96%). The treatment of diarrhea was antidiarrheal (44.81%), fluid rehydration (32.55%), and antibiotics (22.64%). Most patients left the hospital in an improved condition and were allowed to go home (92%). There is a significant relationship between the use of zinc, probiotics, and a combination of zinc and probiotics on LoS.